THEORETICAL FOUNDATIONS OF ATTRACTING INVESTMENTS - Xolniyozov Asror (Zamonaviy ilmiy yondashuvlar va texnologik taraqqiyotning ustuvor yo‘nalishlari, 2026)
This article discusses the theoretical foundations of attracting investments, the economic essence of the concept of investment, and the main types of investments. It also analyzes the key factors influencing investment attraction, the importance of the investment climate in the economy, and modern investment approaches. Special attention is given to the role of investments in the economic development of a country, the significance of attracting foreign investments, and issues related to improving investment policy. As a result of the research, conclusions and recommendations were developed for improving the investment environment and increasing investment activity.